AUTOCHARGE: AUTOMATICALLY CHARGE SMARTPHONE USING LIGHT BEAM (JournalNX - A Multidisciplinary Peer Reviewed Journal, 2021)
Today's smartphones are very power hungry. They use powerful hardware including multicore CPU, many GPU cores, large screen and high-speed wireless network interfaces, all with a high power consumption. They also run many energy-expensive applications such as high-end games, full HD video playback, and various continuous sensing tasks for context awareness. As a result, many users suffer from a short battery lifetime on their smartphones and thus they often have to recharge their smartphones every day or even multiple times per day. To make user put in less efforts and have a full battery every time they use their smartphone we have researched the idea of AutoCharge. The idea was conceived by Microsoft [1], but their design was a costly affair for the regular consumer. Taking inspiration from Microsoft we have made a prototype which can cater users from all walks of life.